Clinical Evaluation of Amyloid-Related Imaging Abnormalities in Bapineuzumab Phase III Studies. - Brashear, H Robert; Ketter, Nzeera; Bogert, Jennifer; Di, Jianing; Salloway, Stephen P; Sperling, Reisa (J Alzheimers Dis, 2018)
BACKGROUND: Amyloid-related imaging abnormalities with effusion or edema (ARIA-E) reported in patients with mild-to-moderate Alzheimer's disease in bapineuzumab phase III studies. OBJECTIVES: Assess symptoms, clinical severity, and ARIA-E outcomes, and to evaluate effects on cognition and function. METHODS: A centralized systematic sequential locked procedure and scoring system for assessment of magnetic resonance imaging scans in 1,331 APOE ɛ4 noncarriers and 1,121 carriers was conducted by experienced and trained pairs of neuroradiologists. RESULTS: Treatment-emergent ARIA-E occurred in 15.8% of bapineuzumab and 0.8% placebo-treated patients. In all treated APOE ɛ4 noncarriers, the percentage of patients with ARIA-E was 5.6%, 13.4%, and 19.9% in the 0.5, 1.0, and 2.0 mg/kg groups respectively, and the incidence of symptomatic ARIA-E was 1.5%, 1.5%, and 7.8%, respectively. In carriers, ARIA-E occurred in 21.2% in the 0.5 mg/kg group, and symptomatic ARIA-E occurred in 2.4%. The clinical severity of ARIA-E in those patients in whom it was detected during the study was mild in 57.1%, 61.3%, and 50.0% of cases in 0.5, 1.0, and 2.0 mg/kg noncarriers respectively, and in 73.8% of cases in 0.5 mg/kg carriers. Vascular risk factors did not appear to increase susceptibility to ARIA-E. Rate of decline in cognition and function measured by changes in ADAS-Cog/11 and DAD total scores did not meaningfully differ in patients with ARIA-E versus those without ARIA-E. Extent of cognitive decline was similar over all visit intervals. CONCLUSIONS: Overall, ARIA-E was mild and asymptomatic. ARIA-E did not demonstrate clinically meaningful acute or chronic impact on cognition or function.Registration: NCT00574132 (Bapineuzumab-301), NCT00575055 (Bapineuzumab-302).

BACE1 Dynamics Upon Inhibition with a BACE Inhibitor and Correlation to Downstream Alzheimer's Disease Markers in Elderly Healthy Participants. - Timmers, Maarten; Barão, Soraia; Van Broeck, Bianca; Tesseur, Ina; Slemmon, John; de Waepenaert, Katja; Bogert, Jennifer; Shaw, Leslie M; Engelborghs, Sebastiaan; Moechars, Dieder; Mercken, Marc; Van Nueten, Luc; et al. (J Alzheimers Dis, 2017)
The β-site amyloid-β protein precursor (AβPP) cleaving enzyme-1 (BACE1) is the rate limiting enzyme in the generation of amyloid-β peptide (Aβ) from AβPP, one of the major pathways in Alzheimer's disease (AD) pathology. Increased BACE1 levels and activity have been reported in the brain of patients with sporadic AD. Therefore, changes of BACE1 levels in the cerebrospinal fluid (CSF) have also been investigated as a possible biomarker of the disease. We analyzed BACE1 levels in CSF of elderly healthy participants before and after chronic treatment with a BACE inhibitor (BACEi) and evaluated the correlation between BACE1 levels and downstream AD markers. Overall, BACE1 CSF levels showed strong correlations to all downstream AD markers investigated. This is the first reported finding that shows BACE1 levels in CSF were well correlated to its end product Aβ1 - 42. As previously described, BACE1 levels were strongly correlated to total-tau and phosphorylated tau levels in CSF. Generally, chronic BACE inhibition did not influence BACE1 CSF protein levels. Follow-up studies including early-stage AD pathophysiology and prodromal AD patients will help to understand the importance of measuring BACE1 routinely in daily clinical practice and AD clinical trials.

Central Review of Amyloid-Related Imaging Abnormalities in Two Phase III Clinical Trials of Bapineuzumab in Mild-To-Moderate Alzheimer's Disease Patients. - Ketter, Nzeera; Brashear, H Robert; Bogert, Jennifer; Di, Jianing; Miaux, Yves; Gass, Achim; Purcell, Derk D; Barkhof, Frederik; Arrighi, H Michael (J Alzheimers Dis, 2017)
BACKGROUND: Amyloid-related imaging abnormalities (ARIA) consist of ARIA-E (with effusion or edema) and ARIA-H (hemosiderin deposits [HDs]). OBJECTIVES: To address accurate ascertainment of ARIA identification, a final magnetic resonance imaging (MRI) reading was performed on patients with mild-to-moderate Alzheimer's disease randomized to bapineuzumab IV or placebo during two Phase III trials (APOE ɛ4 allele carriers or noncarriers). METHODS: Final MRI central review consisted of a systematic sequential locked, adjudicated read in 1,331 APOE ɛ4 noncarriers and 1,121 carriers by independent neuroradiologists. Assessment of ARIA-E, ARIA-H, intracerebral hemorrhages, and age-related white matter changes is described. RESULTS: In the Final Read, treatment-emergent ARIA-E were identified in 242 patients including 76 additional cases not noted previously in real time. Overall, incidence proportion of ARIA-E was higher in carriers (active 21.2%; placebo 1.1%) than in noncarriers (pooled active 11.3%; placebo 0.6%), and was more often identified in homozygote APOE ɛ4 carriers than heterozygotes (34.5% versus 16.9%). Incidence rate of ARIA-E increased with increased dose in noncarriers. Frequency of ARIA-E first episodes was highest after the first and second bapineuzumab infusion and declined after repeated infusions. Incidence of total HDs <10 mm (cerebral microhemorrhages) was higher in active groups versus placebo. CONCLUSION: ARIA was detected more often on MRI scans when every scan was reviewed by trained neuroradiologists and results adjudicated. There was increased incidence of ARIA-E in bapineuzumab-treated carriers who had a microhemorrhage at baseline. ARIA-E was a risk factor for incident ARIA-H and late onset ARIA-E was milder radiologically. Age-related white matter changes did not progress during the study.